ASPEK HUKUM PEMBERLAKUAN PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) DALAM RANGKA PENANGANAN CORONA VIRUS DISEASE 2019 (COVID-19) - Hasrul, Muh (Jurnal Legislatif, 2020)
Abstract In order to attempt reduction made the implementation of health quarantine as stipulated in Law Number 6 Year 2018 on Health Quarantine. The spread of Corona Virus Disease in 2019 (Covid-19) in Indonesia is increasing and expanding cross-region and cross-country accompanied by the number of cases and/or the number of deaths. The increase in the impact on aspects of political, economic, social, cultural, defense and security, as well as the welfare of the people in Indonesia, so that the necessary acceleration of the handling of the Covid-19 in the form of restrictive measures Large-Scale Social in order to suppress the spread of Covid-19 more widespread. Such measures include restrictions on the activities of certain residents in a region suspected of being infected Covid-19 including restrictions on the movement of people and/or goods to one province or specific districts and cities to prevent the spread of Covid-19.This paper aims to examine and discuss the legal aspects related to the Restrictions Large-scale Social (PSBB). Keywords: Legal Aspects; Covid-19; PSBB; Abstrak Dalam rangka upaya penanggulangan dilakukan penyelenggaraan kekarantinaan kesehatan sebagaimana telah diatur dalam Undang-Undang Nomor 6 Tahun 2018 tentang Kekarantinaan Kesehatan. Penyebaran Corona Virus Disease 2019 (COVID-19) di Indonesia saat ini sudah semakin meningkat dan meluas lintas wilayah dan lintas negara yang diiringi dengan jumlah kasus dan/atau jumlah kematian. Peningkatan tersebut berdampak pada aspek politik, ekonomi, sosial, budaya, pertahanan dan keamanan, serta kesejahteraan masyarakat di Indonesia, sehingga diperlukan percepatan penanganan Covid-19 dalam bentuk tindakan Pembatasan Sosial Berskala Besar dalam rangka menekan penyebaran Covid-19 semakin meluas. Tindakan tersebut meliputi pembatasan kegiatan tertentu penduduk dalam suatu wilayah yang diduga terinfeksi Covid-19 termasuk pembatasan terhadap pergerakan orang dan/atau barang untuk satu provinsi atau kabupaten/kota tertentu untuk mencegah penyebaran Covid-19.Tulisan ini betujuan untuk mengkaji dan membahas aspek hukum yang berkaitan dengan Pembatasan Sosial berskala Besar (PSBB). Kata Kunci: Aspek Hukum; Covid-19; PSBB;